Thermospheric Neutral Density Variation During the "SpaceX" Storm: Implications From Physics‐Based Whole Geospace Modeling. Issue 12 (29th November 2022) - Lin, Dong; Wang, Wenbin; Garcia‐Sage, Katherine; Yue, Jia; Merkin, Viacheslav; McInerney, Joseph M.; Pham, Kevin; Sorathia, Kareem
Abstract: The Starlink satellites launched on 3 February 2022 were lost before they fully arrived in their designated orbits. The loss was attributed to two moderate geomagnetic storms that occurred consecutively on 3–4 February. We investigate the thermospheric neutral mass density variation during these storms with the Multiscale Atmosphere‐Geospace Environment (MAGE) model, a first‐principles, fully coupled geospace model. Simulated neutral density enhancements are validated by Swarm satellite measurements at the altitude of 400–500 km. Comparison with standalone TIEGCM and empirical NRLMSIS 2.0 and DTM‐2013 models suggests better performance by MAGE in predicting the maximum density enhancement and resolving the gradual recovery process. Along the Starlink satellite orbit in the middle thermosphere (∼200 km altitude), MAGE predicts up to 150% density enhancement near the second storm peak while standalone TIEGCM, NRLMSIS 2.0, and DTM‐2013 suggest only ∼50% increase. MAGE also suggests altitudinal, longitudinal, and latitudinal variability of storm‐time percentage density enhancement due to height dependent Joule heating deposition per unit mass, thermospheric circulation changes, and traveling atmospheric disturbances. This study demonstrates that a moderate storm can cause substantial density enhancement in the middle thermosphere. Thermospheric mass density strongly depends on the strength, timing, and location of high‐latitude energy input, which cannot be fully reproduced with empirical models. A physics‐based, fully coupled geospace model that can accurately resolve the high‐latitude energy input and its variability is critical to modeling the dynamic response of thermospheric neutral density during storm time. Plain Language Summary: On 3 February 2022, 40 Starlink satellites were launched by the SpaceX Corporation when a moderate geomagnetic storm occurred, followed by another storm on 4 February. The storm activities have been regarded as the culprit for the loss the Starlink satellites afterward. Although strong geomagnetic storms are well‐known to be able to increase the neutral atmospheric mass density so as to satellite drag in the thermosphere where many space vehicles are orbiting around the Earth, a not‐so‐strong storm was not expected to bring such huge impacts based on engineering design evaluation using empirical atmospheric density models. This study compares the performance of a state‐of‐the‐art physics‐based, fully coupled whole geospace model and empirical models in predicting the neutral mass density variation in the thermosphere. It turns out that the physics‐based model is more accurate in capturing the magnitude of storm enhancement of neutral density. It also resolves the gradual recovery process even though it is not reflected in some geomagnetic indices that are used to drive the empirical models. Using such a first‐principles whole geospace model is suggested as a necessary step in future space weather applications. Key Points: Our model predicts up to ∼150% enhancement in neutral density along Starlink orbit during a moderate geomagnetic storm on 3–4 February 2022 Empirical models tend to underestimate storm effects in thermospheric density enhancement The whole geospace model resolves the gradual recovery and wave perturbations missed by empirical models